Interaction and binding mechanism of cyanidin-3-O-glucoside to ovalbumin in varying pH conditions: A spectroscopic and molecular docking study. (1st August 2020) - Fu, Xizhe; Belwal, Tarun; He, Yihan; Xu, Yanqun; Li, Li; Luo, Zisheng
Highlight: Interaction mechanism between OVA and C3G at different pH were firstly studied. Hydrogen bond and van der Waals were the main driving forces. OVA showed higher binding affinity towards C3G in neutral condition. Secondary structure of OVA was changed in a similar way during binding at both pH. Surface hydrophobicity of OVA decreased while thermostability of C3G increased. Abstract: Egg ovalbumin (OVA) as a prevalent dietary protein and has the potential to serve as a carrier for unstable bioactive compounds, however, understanding their interaction mechanism is the preliminary step. In this work, the interactions between cyanidin-3-O-glucoside (C3G) and OVA in both acidic and neutral pH environment were investigated by spectroscopic methods and molecular docking analysis. The results revealed that fluorescence quenching mechanism of OVA-C3G was predominantly static. The main acting forces were hydrogen bonds and van der Waals forces under varying pH conditions. However, the binding affinity of C3G to OVA was higher in neutral environment than that in acidic condition. The binding of C3G slightly increased the diameter of the complex, resulting in increase of α-helix, decrease of β-turn, random coil, and total main secondary structure. Moreover, the thermostability of C3G was significantly improved after OVA addition, suggesting its promising application in functional foods.